Association of aortic vascular uptake of 18FDG by PET/CT and aortic wall thickness by MRI in psoriasis: A prospective observational study - Groenendyk, Jacob W. (Eur J Nucl Med Mol Imaging, 2019)
BACKGROUND: The contribution of inflammation to the incidence of cardiovascular disease (CVD) has been increasingly recognized in recent years. We investigated the relationship of aortic vascular uptake of 18F-FDG by PET/CT and aortic wall thickness (AWT) by MRI in psoriasis, a chronic inflammatory disease with increased incidence of CVD.165 patients with plaque psoriasis participated in an ongoing longitudinal cohort study. Subclinical atherosclerosis was assessed as aortic uptake of 18F-FDG by PET/CT reported as target to background ratio (TBR) and AWT by MRI reported as maximal thickness. RESULTS: Patients with psoriasis were middle-aged, predominantly male and had mild CV risk by traditional risk factors. Psoriasis severity as measured by PASI score was a notable determinant of AWT (ρ=0.20, p=0.01). Moreover, aortic vascular uptake of 18F-FDG associated with AWT by MRI at baseline in unadjusted analysis (β=0.27 p=0.001) and following adjustment for traditional cardiovascular risk factors, waist-to-hip ratio and statin use (β=0.21 p=0.01). Finally, following one year of psoriasis treatment, a decrease in aortic vascular uptake of 18F-FDG was associated with a reduction in AWT in fully adjusted models (β=0.33, p=0.02). CONCLUSION: In conclusion, we demonstrate that psoriasis severity and aortic vascular uptake of 18F-FDG in the aorta were associated with AWT. Following treatment of psoriasis, a decrease in aortic vascular uptake of 18F-FDG was associated with a reduction in AWT at one-year. These findings suggest that aortic vascular uptake of 18F-FDG is associated with early evidence of vascular disease assessed by aortic wall thickness. Prospective studies in larger populations including other inflammatory diseases are warranted.